2018
DOI: 10.1177/0146167218757455
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Social Dominance Theory and System Justification: The Role of Social Status in 19 Nations

Abstract: This study tests specific competing hypotheses from social dominance theory/realistic conflict theory (RCT) versus system justification theory about the role of social status. In particular, it examines whether system justification belief and effects are stronger among people with low socioeconomic status, and in less socially developed and unequal nations than among better-off people and countries. A cross-national survey was carried out in 19 nations from the Americas, Western and Eastern Europe, Asia, and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
101
2
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 99 publications
(140 reference statements)
12
101
2
14
Order By: Relevance
“…As we discuss below, the foregoing cases of system justification seem more prominent when social identification is strong rather than weak, a finding that has received support in a recent 19‐nation study by Vargas‐Salfate, Paez, Liu, Pratto, and Gil de Zúñiga () and a modest but still positive support in 66 independent laboratories spread across 30 nations (Brandt et al ., ). Hence, an autonomous system justification motivation that works against the collective interests of the disadvantaged does not seem theoretically viable (Owuamalam, Rubin, & Spears, ) or empirically evident when the optimal conditions for cognitive dissonance are considered (Brandt, ).…”
Section: The System Justification Motivationmentioning
confidence: 81%
“…As we discuss below, the foregoing cases of system justification seem more prominent when social identification is strong rather than weak, a finding that has received support in a recent 19‐nation study by Vargas‐Salfate, Paez, Liu, Pratto, and Gil de Zúñiga () and a modest but still positive support in 66 independent laboratories spread across 30 nations (Brandt et al ., ). Hence, an autonomous system justification motivation that works against the collective interests of the disadvantaged does not seem theoretically viable (Owuamalam, Rubin, & Spears, ) or empirically evident when the optimal conditions for cognitive dissonance are considered (Brandt, ).…”
Section: The System Justification Motivationmentioning
confidence: 81%
“…In contrast, a leader that advocates substantive social change to achieve group‐based interests should experience increased support when group‐based concerns are salient, but decreased support when system justification concerns are salient. Consideration of when the system justification motive will elicit general or domain‐specific status quo defence (Jost & Kay, ) is also important; recent research has suggested that this distinction moderates the relationship between social status and system justification (Sengupta et al ., ; see also Brandt, ; Vargas‐Salfate, Paez, Liu, Pratto, & Gil de Zúñiga, ).…”
Section: Introductionmentioning
confidence: 96%
“…In fact, to the extent that system justification conflicts with motives for self‐enhancement, self‐interest, and ingroup favoritism among members of disadvantaged groups… it should often be tempered by these other motives' (p. 17). Thus, we never regarded dissonance reduction as the ‘engine' of system justification, as an increasing number of scholars appear to have mistakenly assumed (Brandt, ; Caricati, ; Caricati & Sollami, ; Owuamalam et al ., 2016b; Owuamalam, Rubin, & Spears, , ; Vargas‐Salfate et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Brandt found scant evidence of enhanced system justification among the disadvantaged – but he also found little or no consistent evidence of group‐based self‐interest. His null results are therefore equally at odds with theories of realistic group conflict, social identification, and social dominance (see Caricati & Sollami, ; Vargas‐Salfate et al ., ). As I have argued elsewhere (Jost, ), we must still confront a fundamental question in social science: Why is it that members of the working class are just as likely – or, in other cases, almost as likely – as the middle and upper classes to defend and justify the societal status quo?…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation